2005
DOI: 10.1029/2004wr003779
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of mountain stream morphology

Abstract: [1] We use a large and diverse data set from mountain streams around the world to explore relationships between reach-scale channel morphology and control variables. The data set includes 177 step-pool reaches, 44 plane-bed reaches, and 114 pool-riffle reaches from the western United States, Panama, and New Zealand. We performed several iterations of stepwise discriminant analysis on these data. A three-variable discriminant function using slope (S), D 84 , and channel width (w) produced an error rate of 24% f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 32 publications
4
85
0
Order By: Relevance
“…It should also be noted that the inclusion of slope lessened the statistical significance of the predictive models. This was not expected since slope has been found to be a good predictor for reach average conditions (Wohl et al, 2004;Wohl and Merritt, 2005;Thompson et al, 2006). While the bivariate model of ln(S) did out perform other predictor variables, it did not perform as well as w* or the remaining variables in Equation (4) ( Table II).…”
Section: Statistical Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…It should also be noted that the inclusion of slope lessened the statistical significance of the predictive models. This was not expected since slope has been found to be a good predictor for reach average conditions (Wohl et al, 2004;Wohl and Merritt, 2005;Thompson et al, 2006). While the bivariate model of ln(S) did out perform other predictor variables, it did not perform as well as w* or the remaining variables in Equation (4) ( Table II).…”
Section: Statistical Resultsmentioning
confidence: 75%
“…Individual variables that were found to be most descriptive in predicting a dominant clustered topography on the three rivers examined were w, d 84 and Q. Wohl and Merritt (2005) also found w and d 84 to be useful in predicting reach morphology, but they found that S rather than Q was also important. Non-dimensional forms of these variables, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In previous catchment-scale analyses, the importance of correctly determining channel slope from available data sources has been recognised as a key factor in model performance Wohl and Merritt, 2005). For this study, modelled slopes compare well to surveyed reach slopes and show a significant correlation (R 2 = 0.66; p b 0.001; Fig.…”
Section: Reach Slopementioning
confidence: 60%
“…Recent evaluations of mountain stream channel morphology suggest channel slope is the dominant discriminating variable (Montgomery and Buffington, 1997;Wohl and Merritt, 2005;Thompson et al, 2006). For Southeast Australian mountain streams Thompson et al (2006) indicated that catchment lithology and contributing catchment area are also required to discriminate between some reach morphologies.…”
Section: Methodsmentioning
confidence: 98%
“…Kaufmann (1987a), however, showed that hydraulic resistance was inversely related to the relative submergence of bedforms and other large-scale roughness elements (riffles, pools, steps), and these could be quantified by the ratio of mean thalweg depth (d th ) to mean thalweg residual depth (d res ). He interpreted d th /d res as an expression of relative submergence of bedforms (e.g., riffles and pools), analogous in concept to Wohl and Merritt's (2005) definition of "relative form roughness," the ratio of hydraulic radius to bedform height (which is actually a relative submergence index). The inverse hydraulic resistance measure, (8/f t ) 0.5 = U/U⁎ = (U 2 /gRS) 0.5 , back-calculated from mean advective dye transport velocity, was log-linearly related to relative submergence of residual depth [(8/f) 0.5 = 0.62 Ln(d th / d res ), R 2 = 0.57, n = 40].…”
Section: Influence Of Form Roughnessmentioning
confidence: 98%